Design and development of a comprehensive carbon footprint calculation model for academic programs of University Tenaga Nasional - K Krishnan a/l Kumarasan (2023)
The purpose of this research is to calculate out the amount of carbon discharge by a student in Universiti Tenaga Nasional (UNITEN).